Can facts trump unconditional trust? Evidence-based information halves the influence of physicians' non-evidence-based cancer screening recommendations - Odette Wegwarth; Gert G. Wagner; Gerd Gigerenzer (PLOS ONE, 2017)
Informed decision making in medicine, defined as basing one's decision on the best current medical evidence, requires both informed physicians and informed patients. In cancer screening, however, studies document that these prerequisites are not yet met. Many physicians do not know or understand the medical evidence behind screening tests, do not adequately counsel (asymptomatic) people on screening, and make recommendations that conflict with existing guidelines on informed choice. Consistent with this situation, nation-wide studies showed that the general public misperceives the contribution of cancer screening but that understanding considerably improves when evidence-based information is provided. However, can evidence-based patient information about cancer screening make people also less likely to simply follow a physician's non-evidence-based advice? A national sample of 897 German citizens, surveyed in face-to-face computer-assisted personal interviews, received either evidence-based (e.g., absolute risks on benefits and harms; n = 451) or non-evidence-based (e.g., relative risks on benefits only; n = 446) patient information about a cancer screening test and were then asked to make their initial cancer screening choice. Thereafter, participants received a hypothetical physician's recommendation, which was non-evidence-based in terms of existing guidelines on informed decision making (i.e., reporting either benefits or harms but not both; no provision of numbers). When provided with non-evidence-based patient information (n = 446), a mean of 33.1% of 235 participants whose initial screening choice contradicted the hypothetical physician's non-evidence-based recommendation adjusted their choice in deference to that recommendation (95% CI: 27.4 to 39.4%), whereas with evidence-based patient information (n = 451), only half as many, a mean of 16.0% of 225 (95% CI: 11.8 to 21.4%), modified their choice. Thus, evidence-based patient information makes people less likely to simply follow non-evidence-based recommendations of physicians and supports people in making evidence-based decisions even when not adequately counseled on cancer screening.
Keywords: 330